Impact of error self-perception of aerobic capacity in the safety and efficacy of the lifeguards. Issue 1 (2nd January 2016) - Prieto, Jose A.; Nistal, Paloma; Méndez, David; Abelairas-Gomez, Cristian; Barcala-Furelos, Roberto
Abstract : Introduction . The strong physical demands that are required of lifeguards during rescues also require an accurate self-perception of one's fitness level to be able to regulate the intensity of effort. Objectives . The aim of this study was to determine the real aerobic capacity (RAC) and to compare it with two self-reported measurements: subjective appraisal of aerobic capacity (SAAC) and appraisal of physical exercise (APE). Methods . Fifty-two professional lifeguards were included in the study. For an objective assessment of RAC, the lifeguards' maximum oxygen uptake ( V O2max ) values were measured during treadmill stress tests. A fitness assessment questionnaire was used to obtain the SAAC and APE values. Results . We found a statistically significant association between the APE and RAC variables in the contingency analysis ( p < 0.001). In total, 93.7% of the lifeguards who obtained a V O2max value below 43 ml kg −1 min −1 considered their aerobic capacity to be high or very high . Conclusion . This self-perception error of true aerobic capacity could lead to premature fatigue during a rescue, endangering both the lifeguard's life and the life of the victim. These data may help lifeguards and beach managers to become aware of the need to know lifeguards' true physical conditions through testing and structured training programs.